Legal obligations of pharmaceutical products as guarantees for consumer protection - Soumia, Belmerabet; El Amine, Dhamene Mohamed (The International tax journal, 2025)
In the context of product liability rules, pharmaceutical manufacturers have several key obligations, including informing consumers, ensuring product safety, and providing guarantees against hidden defects. They must also comply with established production standards and norms. However, manufacturers’ responsibility is heightened in the case of pharmaceutical products, given their significant impact on human health and safety.